2006
DOI: 10.4049/jimmunol.176.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Rejection Requires STAT5a/b-Regulated Antiapoptotic Activity in T Cells but Not B Cells

Abstract: STATs play key roles in immune function. We examined the role of STAT5a/b in allograft rejection. STAT5a/b-deficient mice showed a 4-fold increased survival time of heart allografts (p < 0.01). Unlike wild type, purified STAT5a/b−/− T cells transferred to Rag1−/− recipients failed to mediate heart allograft rejection until supplemented with STAT5a/b−/− B cells. In vitro, STAT5a/b−/− T cells did not proliferate in response to Con A or alloantigens but entered apoptosis within 48 h (95%). Activated STAT5a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Lack of IL-2-driven CD4 ϩ CD25 ϩ natural regulatory cells in Stat5a/b Ϫ/Ϫ mice disturbed homeostasis of self-tolerance leading to autoimmune diseases (75 ; Table 1A). Our recent results showed that Stat5a/b-deficient T cells failed to mediate allograft rejection (76), which coincided with apoptosis and elevated expression of multiple pro-apototic genes. Stat5a/b-deficiency had no impact on B cells and their in vivo production of alloantigen-specific IgM and IgG antibodies.…”
Section: The Role Of Stats In Lymphoid Cell Functionmentioning
confidence: 98%
“…Lack of IL-2-driven CD4 ϩ CD25 ϩ natural regulatory cells in Stat5a/b Ϫ/Ϫ mice disturbed homeostasis of self-tolerance leading to autoimmune diseases (75 ; Table 1A). Our recent results showed that Stat5a/b-deficient T cells failed to mediate allograft rejection (76), which coincided with apoptosis and elevated expression of multiple pro-apototic genes. Stat5a/b-deficiency had no impact on B cells and their in vivo production of alloantigen-specific IgM and IgG antibodies.…”
Section: The Role Of Stats In Lymphoid Cell Functionmentioning
confidence: 98%
“…The cytokine signals leading to T cell activation and proliferation involve binding of common γ-chain (γc) cytokines (interleukin (IL)-2, IL-4, IL-7, IL-9, IL-15 and IL-21) to their cognate receptors which in-turn activates Janus tyrosine kinases (Jak) 1 or Jak3 in the downstream milieu inducing transcription of multiple genes through signal transducers and activators of transcription (Stat)3, Stat6 and Stat5a/b pathways [1]. Among these cytokines, IL-2 is the major growth factor optimizing T cell responses as signaling through its high affinity IL-2 receptor (consisting of the α, β and common γ chains) and the Jak3-Stat5 axis is essential for the survival, proliferation and differentiation of antigen-activated T cells [2][5]. Naïve and memory T cells lack IL-2Rα (CD25) expression, but its expression is induced soon after antigen activation.…”
Section: Introductionmentioning
confidence: 99%
“…Activated ∆NSTAT5a/b -/-T cells produced cytokines but failed to proliferate and instead entered apoptosis. Apoptosis of T cells correlated with increased expression of multiple proapototic genes (Bok, Blk, Bax, Bcl10, Nip3Myd88, Fadd), as revealed by microarray analysis [150]. Furthermore, only activated STAT5a/b--deficient T cells had decreased expression of antiapoptotic Bcl2 and induced proapoptotic Bak mRNA.…”
Section: Lessons From Stat Knockoutsmentioning
confidence: 94%